PERBANDINGAN PERTIMBANGAN HAKIM PADA PUTUSAN NOMOR 375 K/Pdt.Sus.HKI/2020 DAN PUTUSAN NOMOR 20 PK/Pdt.Sus-HKI/2021 DALAM KASUS PENEMU PERTAMA MEREK EIGER YANG LALAI MENDAFTARKAN MEREKNYA - Yori, Aurelius Kasimirus; Sutanto, Very Werson; Putri, Azalia Hardi (Gapenas Publisher, 2024)
Both of the decision reflected judge’s scale priority. Decision Numb.375/Pdt.Sus.HKI/2020 emphasized the fulfillment of justice and expediency aspect. Judge was not merely as an exsecutor or mouthpiece of law, but also as an agent of law engineering. Meanwhile, on Decision Numb.20 PK/Pdt.Sus-HKI/2021, judge prioritized the aspect of legal certainty by deciding based on written norm (UU Merek) or in other words “quod scripti, scripti